System and engineering practice of coal mining technology under buildings, water bodies and railways in China - Wenbing GUO; Yuhang HU; Chaoqun HU; Longxiang LI; Dongtao WU; Zhibo GE (Meitan kexue jishu)
There is a large amount of coal resources that are difficult to mine due to buildings, water bodies and railways in China. Conducting research on coal mining technology and liberating pressed coal under building, water body and railways are significant for improving the recovery rate of coal resources, optimizing the layout of mining and extending the service years of mines. The paper summarized the coal mining technology under buildings, water bodies and railways and buildings and structures protection technologies in China, including partial mining, filling mining, coordinated mining, overburden bed separation grouting technology and ground protection, repair and reinforcement techniques, the advantages, disadvantages and applicable conditions of each technique are also analyzed. It is proposed that the source of damage to buildings and structures caused by coal mining under buildings, water bodies and railways is the overburden destruction and surface movement. Controlling surface subsidence and studying the law of surface movement and deformation are the key to coal mining under buildings and structures. Reducing overburden failure and accurately predicting overburden failure height are the key to safe coal mining technology under water bodies (overburden aquifers). Comprehensively analyzed the law of over-burden destruction and surface movement, the prediction of surface movement and deformation, and the protection technology of ground buildings under buildings, water bodies and railways from the experience formula, theoretical calculations, and on-site measurements. Research considers that high efficiency, low cost, all solid waste, intelligent overburden grout injection and filling mining, groundwater in-situ protection and other sources of subsidence reduction technology will be the development direction of coal mining technology under building, water body and railways in the future, and establish the “space-air-ground-well” integrated monitoring and early warning mechanism of overburden and surface movement and deformation, strengthen the improvement of coal mining technology under buildings, water bodies and railways, all solid waste materials, technology and equipment level, scientifically construct and continuously improve the green low-carbon, intelligent, safe and efficient mining technology system under buildings, water bodies and railways.